2012
DOI: 10.1037/a0024934
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal examination of coach and peer motivational climates in youth sport: Implications for moral attitudes, well-being, and behavioral investment.

Abstract: The results indicate the importance of considering peer influence in addition to coach influence when examining motivational climate in youth sport.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
110
1
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(133 citation statements)
references
References 66 publications
(93 reference statements)
12
110
1
5
Order By: Relevance
“…Our findings provide support for the direct positive effect of a peer task motivational climate at the team level on sport enjoyment and commitment, which was consistent with our hypotheses based on propositions that athletes report positive outcomes when they are on teams that have a high task peer climate (Ntoumanis et al, 2012). These findings further emphasize the importance of a team-level task peer climate as a possible protective factor for adolescent athletes' sport enjoyment and commitment.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Our findings provide support for the direct positive effect of a peer task motivational climate at the team level on sport enjoyment and commitment, which was consistent with our hypotheses based on propositions that athletes report positive outcomes when they are on teams that have a high task peer climate (Ntoumanis et al, 2012). These findings further emphasize the importance of a team-level task peer climate as a possible protective factor for adolescent athletes' sport enjoyment and commitment.…”
Section: Discussionsupporting
confidence: 80%
“…Researchers have argued that perceptions of the peer motivational climate appear to vary between teams (Vazou, 2010) and that the motivational climate should be studied as a team-level variable within sport settings (Papaioannou, Marsh, & Theodorakis, 2004). In a year-long study, Ntoumanis, Taylor, and Thogersen-Ntoumani (2012) reported that athletes on teams with higher average perceptions of a peer task climate showed greater positive and prosocial attitudes in sport, greater subjective vitality and commitment, and decreased burnout. In contrast, athletes on teams with higher perceptions of a peer ego climate displayed higher levels of antisocial attitudes (i.e., endorsement of cheating) and burnout, and an ego peer climate was negatively associated with commitment.…”
Section: A Multilevel Model Of Emotion Regulation Of Athletes In Teamsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it must be emphasized that there will always be athletes who are judged to be below average in ability, regardless of whether athletes are brought together or kept apart on the basis of their current ability level. Coaches who give ego-involving sports coaching are likely to experience athletes who are in distress, experiencing a state in which their self-esteem is 'on the line,' and thus undergoing more pressure and tension from their coaches (e.g., Deci & Ryan, 1985;Ntoumanis, Taylor, & Thøgersen-Ntoumani, 2012). However, a recent SDT-based study has indicated that only autonomous motivation mediates the association between empathetic concern and helping behaviors, while controlled motivation had no such effect (Pavey, Greitemeyer, & Sparks, 2012).…”
mentioning
confidence: 99%
“…Burada önemli olan nokta bu organizasyonlara etki eden yetişkinler ve diğer akranlar gibi çevresel-sosyal faktörlerdir. Boş zamanda gerçekleştirilen spor aktiviteleri hem kız hem de erkek öğrenciler arasında en popüler aktivitelerin başında gelmektedir (Ntoumanis, Taylor ve Ntoumani, 2012). Bu noktada ebeveynlerin çocuklarına nasıl etki ettiklerini araştırma yönünde yapılan bir çalışmada, genç sporcuların anne ve babalarının etkilerinde kaldıkları ortaya konulmuş ve özellikle babaların daha çok sonuç odaklı hedefler koymalarının ve antrenörlerin de tıpkı babalar gibi bu yönde tutum sergilemelerinin ahlaki karar alma noktasında olumsuz yansımaları olabildiği sonucuna erişilmiştir (Palou ve ark, 2013).…”
Section: Introductionunclassified